Réponses

Meilleure réponse !
2014-04-22T17:43:18+02:00
Bonjour ,
Soit A = (3 x -5) (3 x -5) + (3 x -5) (x + 7) et B = (2x -5) (4x -1) - (x + 2) (2 x -5)
1- a/ Développer et réduire A.
A= (3x -5) (3x-5) +(3x-5)(x-7)
A= 9x² -15x -15x +25 +3x² -21x -5x +35
A= 12x² - 56x + 60
    b/ Calculer A pour x = 2.
A= 12( 2)² - 56(2) +60
A= 48 - 112 +60
A= -4
2- Même questions avec B.
B= (2x-5) (4x -1) -( x+2) (2x-5)
B= 8x² -2x -20x +5 - ( 2x² -5x +4x -10)
B= 8x² -22x +5 -2x² +x +10
B= 6x² -21x +15
b/ Calculer B pour x= 2
B= 6(2)² -21 (2) +15
B= 24 -42 +15
B= -3